Réponses

2013-06-09T13:14:29+02:00

-x+y=-11

2x+y=5

en soustrayant les équations :

2x-(-x) = 5 - (-11)

2x+x = 5 +11

3x = 16

x = 16/3

 

x-3y=0

-x+5y=-1

en ajoutant les équations :

5y-3y = -1

2y = -1

y = -1/2

 

En espérant t'avoir aidé.

2013-06-09T13:58:33+02:00

x-3y=0

-x+5y=-1

-----------

0+2y=-1

2y=-1

y=-1/2

 

x-3y=0

x-3*(-1/2)=0

x+3/2=0

x=-3/2

 

-x+y=-11/ *(-1)

2x+y=5

 

x-y=11

2x+y=5

-------------

3x+0=16

3x=16

x=16/3

 

2x+y=5

2*16/3+y=5

32/3+y=5

y=5-32/3

y=-17/3